2011
DOI: 10.1590/s0100-54052011000300006
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da simulação da solarização do solo com materiais vegetais sobre o crescimento micelial de fungos fitopatogênicos habitantes do solo

Abstract: A incorpora ção de ma teria is vegeta is específicos a ssociados à solarização do solo tem sido um avanço promissor no controle de fungos fitopatogênicos habitantes do solo. O objetivo do trabalho foi a va lia r determina dos efeitos da incorpora çã o e decomposiçã o de brócolis, mamona, mandioca brava e mansa, no solo, em condições de microcosmo mantido em BOD (37±2ºC), sobre o micélio de Fusarium ox yspo ru m f. sp. ly co pe rsic i Ra ça 2 , Mac ro ph o mina p ha seo lina , Rhizoctonia solani AG-4 HGI e de S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
1
4
0
2
Order By: Relevance
“…In this study, we used PDA culture medium and the optimum growth temperature of F. guttiforme isolates was 25°C. This corroborates the data presented by Bueno et al (2007) and Basseto et al (2011), who reported that the optimal temperature range for the growth of the three F. oxysporum strains was from 25 to 26°C.…”
Section: Isolatessupporting
confidence: 92%
“…In this study, we used PDA culture medium and the optimum growth temperature of F. guttiforme isolates was 25°C. This corroborates the data presented by Bueno et al (2007) and Basseto et al (2011), who reported that the optimal temperature range for the growth of the three F. oxysporum strains was from 25 to 26°C.…”
Section: Isolatessupporting
confidence: 92%
“…Esse fitopatógeno pode ter sido favorecido, no referido tratamento, pelos cultivos anteriores com melão, milho e feijão-caupi, todas estas hospedeiras de M. phaseolina (Kimati et al, 2005), e também pelas elevadas temperaturas do solo, que favorecem o seu desenvolvimento, já que é considerado um microrganismo tolerante a altas temperaturas (Basseto et al, 2011).…”
Section: Resultsunclassified
“…The experimental design adopted in this trial was entirely random, with three treatments tested in microcosms involving two bottles connected by a silicone hose that allow air to pass from one flask to another (BASSETO et al, 2011): Treatment 1 = one bottle containing soil + cabbage, and other with six test tubes containing the fungus, all kept in a growth chamber at 40 °C (biofumigation) and 12 h of photoperiod; Treatment 2 = one bottle with distilled water, and other containing six test tubes with the fungus, all kept in a growth chamber at 40 °C and 12 h of photoperiod; and Treatment 3 = one bottle with distilled water, and other containing six test tubes with the fungus, all kept in a growth chamber at 23 °C and 12 h of photoperiod. The treatments were maintained in growth chamber for different periods: 7, 14 and 21 days.…”
Section: Effect Of Disinfection Techniques On the Fungus P Chlamydosporamentioning
confidence: 99%
“…After 4 months, the rootstock cuttings were removed from the substrate and the root system was washed in running water. Then, roots and stem were pruned above the third bud, and 18 cuttings were tied together and placed in one of the flasks of the microcosm (BASSETO et al, 2011).…”
Section: Effect Of Disinfection Techniques On the Fungus P Chlamydosporamentioning
confidence: 99%